Enhancing Sustainable Tourism In East Nusa Tenggara Through Air Transport Connectivity - Prasetya, Oce (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Air transport connectivity is a critical element in supporting tourism in archipelagic regions like East Nusa Tenggara (NTT). This article employs a Systematic Literature Review (SLR) approach to examine key variables in sustainable tourism development, including flight frequency, airport infrastructure, tourist accessibility, and environmental conservation. The analysis reveals that improved air transport connectivity significantly contributes to achieving several Sustainable Development Goals (SDGs), such as SDG 9 (Sustainable Infrastructure), SDG 11 (Sustainable Communities), SDG 13 (Climate Action), and SDG 15 (Biodiversity Conservation). This article provides strategic recommendations for inclusive and environmentally friendly air connectivity development to support tourism growth in NTT.